Interaction Design in Distributed Software Development: practices, challenges, recommendations and research gaps - Alves, Daniel Domingos; Matos, Ecivaldo de Souza (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Human-Computer Interaction (HCI) is an area focused on human interaction with/through computational systems, among which tangent studies on interaction design stand out. In HCI, interaction design has been consolidated as a practice with the potential to support interactive systems projects. On the other hand, more and more organizations are developing software with geographically distributed teams. However, interaction design in distributed software development (DSD) has yet to be explored, mapped, or structured in the scientific literature. Although there are reports in the scientific literature about interaction design in DSD and some proposed solutions, it is still being determined how interaction design occurs in DSD. This research investigated how interaction design has been practiced in DSD, seeking to understand its characteristics, challenges, and limitations. The research methodology was based on Charles S. Peirce’s semiotic methodeutics, bibliographic research method, and mixed methods research to investigate the current state of knowledge and practice on interaction design in DSD. We hope that the results pointed out by this research contribute to the body of knowledge about interaction design at the research frontier between HCI and DSD by (i) providing an overview of research efforts on interaction design in DSD, (ii) providing an overview of the practice of interaction design in DSD, (iii) identify research gaps and discuss future research directions, and (iv) conceiving a set of recommendations for interaction design in DSD.